Preparation method of phenolic resin-based hard carbon, negative pole piece and battery

By combining furfural and carbon nanotubes, phenolic resin-based hard carbon materials were prepared, solving the problems of insufficient reversible capacity and conductivity of phenolic resin-based hard carbon, and achieving high-capacity, high-rate, and long-cycle stable sodium-ion battery performance.

CN121698327APending Publication Date: 2026-03-20TIANJIN POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511879222.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-12
Publication Date
2026-03-20

AI Technical Summary

Technical Problem

Existing phenolic resin-based hard carbon materials suffer from insufficient reversible capacity and poor conductivity, resulting in poor sodium storage and rate performance of sodium-ion batteries.

Method used

By using furfural as a soft template to form a uniform nanoporous structure during carbonization, and adding carbon nanotubes in the prepolymer stage to form a continuous conductive network, combined with optimizing the ratio of active material, conductive agent and binder in the negative electrode sheet, phenolic resin-based hard carbon materials are prepared.

Benefits of technology

Significantly improved reversible capacity and conductivity of hard carbon, achieving sodium-ion battery performance with high capacity, high rate and long cycle stability, with coulombic efficiency maintained above 84% for the first time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121698327A_ABST
    Figure CN121698327A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of phenolic resin-based hard carbon, a negative pole piece and a battery, and the preparation method comprises the following steps: S1, mixing formaldehyde and furfural to obtain a mixed aldehyde solution; s2, adding mixed aldehyde and phenol into a solution containing a basic catalyst, and reacting to generate a liquid phenolic resin prepolymer; s3, adding carbon nanotubes into the liquid phenolic resin prepolymer, and dispersing the carbon nanotubes into the liquid phenolic resin prepolymer to obtain a second prepolymer; s4, curing the second prepolymer to obtain cured resin; and S5, carbonizing the cured resin to obtain phenolic resin-based hard carbon, thereby enhancing the sodium storage capacity and conductivity of the hard carbon.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of sodium ion batteries, and particularly relates to a preparation method of a phenolic resin-based hard carbon, a negative electrode sheet and a battery. BACKGROUND

[0002] Sodium ion batteries have broad application prospects in large-scale energy storage, electric vehicles and other fields due to abundant resources, low cost and high safety. Hard carbon materials have become the mainstream choice for sodium ion battery anodes due to their adjustable interlayer spacing, stable structure and high sodium storage capacity.

[0003] At present, the precursors of hard carbon materials mainly include biomass, natural polymer macromolecules (sucrose, cellulose, lignin, etc.) and synthetic polymer macromolecules (polyacrylonitrile, phenolic resin, etc.). Among them, phenolic resin as a synthetic polymer precursor has the advantages of large capacity potential, controllable composition and structure through the synthesis process, and is expected to further optimize the sodium storage performance. However, the existing phenolic resin-based hard carbon still has two major core problems: one is the insufficient reversible capacity, mainly due to the small number and uneven distribution of closed pore structures suitable for sodium storage in hard carbon, which makes it difficult to provide sufficient sodium storage sites; the other is the poor rate performance, as the limited conductivity of hard carbon and the poor ion and electron transmission path limit the charging and discharging speed.

[0004] In the traditional method of improving the performance of hard carbon, increasing the closed pore structure often relies on the addition of a template agent and then removing it through a complex process, which is cumbersome and costly. To improve the conductivity, the method of mixing conductive agents after carbonization is often used, but the interface between the conductive agent and the hard carbon matrix is not tight and uniform, making it difficult to form a continuous conductive network and fundamentally solving the problem of rate performance.

[0005] Therefore, there is an urgent need to design a preparation method of a phenolic resin-based hard carbon, a negative electrode sheet and a battery to solve the above-mentioned problems. SUMMARY

[0006] The purpose of the present application is to provide a preparation method of a phenolic resin-based hard carbon, a negative electrode sheet and a battery to improve the sodium storage capacity and conductivity of hard carbon.

[0007] To achieve the above-mentioned purpose, the technical solutions of the preparation method of a phenolic resin-based hard carbon, a negative electrode sheet and a battery are as follows: A preparation method of a phenolic resin-based hard carbon, comprising the following steps: S1, mixing formaldehyde and furfural to obtain a mixed aldehyde solution; S2, adding the mixed aldehyde and phenol to a solution containing an alkaline catalyst to react to form a liquid phenolic resin prepolymer; S3, adding carbon nanotubes into the liquid phenolic resin prepolymer and dispersing the carbon nanotubes in the liquid phenolic resin prepolymer to obtain a second prepolymer; S4, curing the second prepolymer to obtain a cured resin; S5, carbonizing the cured resin to obtain a phenolic resin-based hard carbon.

[0008] Further, in step S1, the molar ratio of formaldehyde to furfural is a:(10-a), and a is in the range of 0-10.

[0009] Further, in step S2, the mass ratio of the mixed aldehyde to the phenol is (5-55):100.

[0010] Further, in step S2, the basic catalyst is one or more of LiOH, NaOH, and ammonia water, and the molar addition amount of the basic catalyst is 10%-20% of the molar addition amount of the phenol.

[0011] Further, in step S3, the mass of the carbon nanotubes is 0.5%-2% of the total mass of the formaldehyde, the furfural, and the phenol.

[0012] Further, in step S5, the cured resin is placed in a tube furnace in a nitrogen atmosphere, heated to 1000-1500℃ at a heating rate of 1-5℃ / min, and carbonized for 1-2h to obtain a phenolic resin-based hard carbon.

[0013] Further, in step S5, the furfural acts as a soft template and forms a uniformly dispersed nano-closed pore structure during carbonization; the carbon nanotubes form a continuous conductive network after carbonization and constitute an ion or electron transmission path with the nano-closed pore structure.

[0014] A negative electrode tab includes an electrode material and a current collector, the electrode material includes an active material, a conductive agent, a binder, and a current collector, the active material uses the above-mentioned phenolic resin-based hard carbon, the mass ratio of the active material, the conductive agent, and the binder is (80-95):(2-10):(3-10), and the electrode material is coated on the surface of the current collector.

[0015] Further, the conductive agent is one or more of Super-p, acetylene black, and Ketjen black; and the binder is one or more of sodium alginate, sodium carboxymethyl cellulose, and butadiene styrene rubber.

[0016] A battery includes a negative electrode, a positive electrode, and an electrolyte, and the negative electrode uses the above-mentioned negative electrode tab.

[0017] The preparation method of the phenolic resin-based hard carbon, the negative electrode tab, and the battery have the following advantages: 1、The present application forms pores in situ by furfural soft template without additional template agent and subsequent removal steps, and the process is simple and low in cost; the liquid mixing of formaldehyde and furfural ensures uniform dispersion of furfural, and the nano-closed pore structure formed after carbonization is uniformly distributed, and the sodium storage site is sufficient, so that the reversible capacity of hard carbon is significantly improved, and the highest reversible discharge capacity can reach 418.4 mAh / g (compared with 315.3 mAh / g of traditional hard carbon, an increase of 32.7%).

[0018] 2、The carbon nanotubes are added in the prepolymer stage and dispersed by ultrasonic, and a continuous conductive network is formed after carbonization, which constitutes a "point-surface" transmission path with the closed pore structure, greatly improving the ion and electron transmission efficiency, and significantly optimizing the rate performance of the hard carbon, which can still maintain stable capacity at a high rate of 2 A / g.

[0019] 3、The mass ratio of active material, conductive agent and binder of the negative electrode sheet is optimized, which is matched with the structural characteristics of the phenolic resin-based hard carbon, so as to ensure the balance of the mechanical properties, conductive properties and sodium storage performance of the electrode sheet; the battery using the negative electrode sheet has high capacity, high rate and long cycle stability, and the first coulomb efficiency is maintained at more than 84%, which has high practical value. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 It is a flowchart of the preparation method of the phenolic resin-based hard carbon of the present application; Figure 2 It is a thermogravimetric curve of Comparative Example 1 and Examples 1-3 of the present application; Figure 3 It is an X-ray small-angle diffraction pattern of Comparative Example 1 and Examples 1-3 of the present application; Figure 4 It is a constant current charge-discharge curve of Comparative Example 1 of the present application; Figure 5 It is a constant current charge-discharge curve of Example 1 of the present application; Figure 6 It is a constant current charge-discharge curve of Example 2 of the present application; Figure 7 It is a constant current charge-discharge curve of Example 3 of the present application; Figure 8 It is a rate performance curve of Comparative Example 1 and Examples 1-3 of the present application. DETAILED DESCRIPTION

[0021] In order to make the purposes, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are some but not all of the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative efforts belong to the scope of the present application.

[0022] Those skilled in the art can understand that the combination of features of different embodiments means to be within the scope of the present application and form different embodiments, although some embodiments herein include certain features but not other features included in other embodiments. For example, in the claims, any one of the claimed embodiments can be used in any combination.

[0023] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Figure 1 to the drawings in the embodiments of the present application. Figure 8 A preparation method of a phenolic resin-based hard carbon, a negative electrode sheet and a battery are described.

[0024] A preparation method of a phenolic resin-based hard carbon, comprising the following steps: S1, mixing formaldehyde and furfural to obtain a mixed aldehyde solution; S2, adding the mixed aldehyde and phenol into a solution containing an alkaline catalyst to react to generate a liquid phenolic resin prepolymer; S3, adding carbon nanotubes into the liquid phenolic resin prepolymer and dispersing the carbon nanotubes in the liquid phenolic resin prepolymer to obtain a second prepolymer; S4, curing the second prepolymer to obtain a cured resin; S5, carbonizing the cured resin to obtain a phenolic resin-based hard carbon.

[0025] Further, in step S1, the molar ratio of the formaldehyde to the furfural is a:(10-a), and the value range of a is 0-10.

[0026] Further, in step S2, the mass ratio of the mixed aldehyde to the phenol is (5-55):100.

[0027] Further, in step S2, the alkaline catalyst is one or more of LiOH, NaOH and ammonia water, and the molar addition amount of the alkaline catalyst is 10%-20% of the molar addition amount of the phenol.

[0028] Further, in step S3, the mass of the carbon nanotubes is 0.5%-2% of the total mass of the formaldehyde, the furfural and the phenol.

[0029] Further, in step S5, the solidified resin is placed in a tube furnace in a nitrogen atmosphere, heated to 1000-1500℃ at a heating rate of 1-5℃ / min, carbonized for 1-2h, to obtain a phenolic resin-based hard carbon.

[0030] Further, in step S5, the furfural acts as a soft template to form a uniformly dispersed nano-closed pore structure during carbonization; the carbon nanotubes form a continuous conductive network after carbonization, which forms an ion or electron transport path with the nano-closed pore structure.

[0031] Specifically, in step S1, formaldehyde and furfural are mixed in a molar ratio of a:(10-a), where a ranges from 0 to 10, and stirred until uniformly dispersed to obtain a mixed aldehyde solution.

[0032] Preferably, the formaldehyde is a 37wt% formaldehyde aqueous solution, the furfural has a purity of ≥99wt%, the stirring time is 0.5-2h, and the stirring rate is 100-500r / min, to ensure that the two aldehydes are fully mixed. Both formaldehyde and furfural are liquid, which can achieve molecular-level uniform dispersion, laying a foundation for the formation of a uniform closed pore structure. When a=0, the mixed aldehyde is pure furfural; when a=10, the mixed aldehyde is pure formaldehyde; when a takes a value between 0 and 10, the number and distribution of closed pores can be controlled by adjusting the ratio of the two.

[0033] Specifically, in step S2, the mixed aldehyde obtained in step S1 is added to a solution containing an alkaline catalyst in a mass ratio of (5-55):100, and reacted at 70-95℃ for 1-2h to form a liquid phenolic resin prepolymer. The alkaline catalyst is one or more of LiOH, NaOH, and ammonia water, and the molar addition amount is 10-20% of the molar addition amount of phenol. The alkaline catalyst can efficiently catalyze the polycondensation reaction of formaldehyde, furfural, and phenol, and controlling the reaction temperature and time can ensure that the prepolymer has a suitable degree of polymerization (500-2000), which not only ensures the crosslinking effect of the subsequent curing process, but also avoids excessive polymerization that leads to uneven dispersion of furfural. The mass ratio of mixed aldehyde to phenol is limited to (5-55):100. If the proportion of mixed aldehyde is too low, it is difficult to form sufficient resin skeleton; if the proportion is too high, it is easy to lead to excessive crosslinking of the resin, affecting the formation of closed pores.

[0034] Specifically, in step S3, carbon nanotubes (MWCNTs) are added to the liquid phenolic resin prepolymer generated in step S2, the mass of the carbon nanotubes being 0.5% to 2% of the total mass of formaldehyde, furfural and phenol, the carbon nanotubes are uniformly dispersed in the liquid phenolic resin prepolymer by ultrasonic dispersion, the dispersion time being 0.5 to 2 hours, to obtain a second prepolymer. The carbon nanotubes are preferably carboxylated multi-walled carbon nanotubes, the carboxyl groups on the surface of the carboxylated multi-walled carbon nanotubes can interact with the active groups in the phenolic resin prepolymer, improving the dispersion stability of the carbon nanotubes in the prepolymer; ultrasonic dispersion can effectively prevent the carbon nanotubes from agglomerating, ensuring that they are uniformly distributed in the prepolymer. The amount of carbon nanotubes added is controlled to be 0.5% to 2%, if the amount added is less than 0.5%, a continuous conductive network cannot be formed; if the amount added is more than 2%, the carbon nanotubes are prone to agglomeration, damaging the resin skeleton structure and affecting the integrity of the closed pores.

[0035] Specifically, in step S4, the second prepolymer obtained in step S3 is placed in an environment of 100 to 200°C and cured for 10 to 24 hours to obtain a cured resin. The curing process can cause the phenolic resin prepolymer to undergo crosslinking reactions, forming a three-dimensional network structure, and fixing the carbon nanotubes in the resin skeleton, preventing the carbon nanotubes from migrating and agglomerating during the subsequent carbonization process, and ensuring the continuity of the conductive network. The curing temperature and time need to be strictly controlled, if the temperature is too low or the time is too short, the crosslinking degree of the resin is insufficient and the structural stability is poor; if the temperature is too high or the time is too long, the resin is prone to incomplete carbonization, affecting the performance of the hard carbon in the subsequent process.

[0036] Specifically, in step S5, the cured resin obtained in step S4 is placed in a tube furnace in a nitrogen atmosphere, heated to 1000 to 1500°C at a heating rate of 1 to 5°C / min, and carbonized for 1 to 2 hours to obtain a phenolic resin-based hard carbon. The purity of the nitrogen atmosphere is ≥99.99%, which can prevent oxidation during the carbonization process of the resin, ensuring the integrity of the closed pore structure and the stability of the conductive network. The heating rate is controlled to be 1 to 5°C / min, which can cause the resin to decompose slowly and reduce the collapse of the pores; the carbonization temperature of 1000 to 1500°C is the optimal temperature range for the formation of hard carbon, which can ensure that the resin is fully carbonized and avoid the destruction of the closed pore structure caused by high temperature.

[0037] In this embodiment, furfural acts as a soft template, the furan ring contained in the furfural molecule is easy to decompose at a low temperature of 230°C, and can actively form uniformly dispersed nano-closed pore structures during the carbonization process, which provide sufficient sodium storage sites for sodium ions; at the same time, the carbon nanotubes form a continuous conductive network after carbonization, and together with the nano-closed pore structures, form a "point-surface" combined ion or electron transmission path, accelerating the migration of ions and electrons and simultaneously improving the reversible capacity and rate performance of the hard carbon.

[0038] A negative electrode sheet comprises an electrode material and a current collector, the electrode material comprises an active material, a conductive agent, a binder and a current collector, the mass ratio of the active material, the conductive agent and the binder is (80-95):(2-10):(3-10), and the electrode material is coated on the surface of the current collector.

[0039] Specifically, the current collector material is copper foil or aluminum foil, and the thickness is 8-20 μm; the coating amount of the electrode material is 10-30 mg / cm 2 The corresponding negative electrode sheet surface capacity is 1-3 mAh / cm 2 The proportion of the active material is controlled to be 80-95%, which can guarantee the sodium storage capacity of the negative electrode sheet; the proportion of the conductive agent is 2-10%, which can further supplement the conductive path and synergistically act with the internal conductive network of the hard carbon; and the proportion of the binder is 3-10%, which can ensure the close combination of the electrode material and the current collector, improve the mechanical stability of the sheet, and avoid falling off in the charging and discharging process.

[0040] Further, the conductive agent is one or more of Super-p, acetylene black and Ketjen black; and the binder is one or more of sodium alginate, sodium carboxymethyl cellulose and butadiene styrene rubber.

[0041] A battery comprises a negative electrode, a positive electrode and an electrolyte, and the negative electrode adopts the negative electrode sheet.

[0042] Preferably, the battery is a sodium ion secondary battery, the positive electrode adopts a commonly used positive electrode material of a sodium ion battery (such as a layered oxide, a polyanion compound, etc.), the electrolyte is a 1 mol / L NaPF6 solution of diethylene glycol dimethyl ether, and the separator is a GF / F type glass fiber separator or other special separator for a sodium ion battery.

[0043] The present application is further illustrated by specific examples below, but the protection scope of the present application is not limited.

[0044] Example 1 Take 4.41g formaldehyde aqueous solution, the mass fraction of formaldehyde aqueous solution is 37wt%, 6g furfural, the molar ratio of formaldehyde to furfural is 7:3, mechanical stirring for 0.5h, get mixed aldehyde solution; The mixed aldehyde solution, 20g phenol, 1.68g NaOH is added to a three-necked flask, NaOH is 15% of the molar amount of phenol, heated to 95℃, stirring for 160min, get liquid phenolic resin prepolymer; The liquid phenolic resin prepolymer is cured at 150℃ for 24h, get the cured resin, the cured resin is placed in a nitrogen atmosphere tube furnace, heated to 1300℃ at 3℃ / min, carbonized for 2h, get phenolic resin based hard carbon, according to the mass ratio of active substance: conductive agent (Super-p): binder (CMC) = 90:5:5, mixed with deionized water to make slurry, coated on the surface of copper foil, vacuum dried at 120℃ for 12h, the sheet is obtained, with metal sodium as the counter electrode, GF / F as the separator, 1mol / L NaPF6 in dimethyl ether solution as the electrolyte, assemble the button cell, stand for 24h, then perform charge-discharge test on the blue cell test system.

[0045] Example 2 Take 3.2g formaldehyde aqueous solution, the mass fraction of formaldehyde aqueous solution is 37wt%, 10g furfural, the molar ratio of formaldehyde to furfural is 5:5, mechanical stirring for 0.5h, get mixed aldehyde solution; The other steps are the same as example 1, get the battery.

[0046] Example 3 The liquid phenolic resin prepolymer in example 1 is used, 1.5wt% of carboxylated multi-walled carbon nanotubes is added to the liquid phenolic resin prepolymer, ultrasonic dispersion for 1h, get the second prepolymer, the second prepolymer is treated according to the steps in example 1, get the battery.

[0047] Comparative example 1 Take 6.3g formaldehyde aqueous solution, the mass fraction of formaldehyde aqueous solution is 37wt%, 0g furfural, the molar ratio of formaldehyde to furfural is 10:0, mechanical stirring for 0.5h, get mixed aldehyde solution; The other steps are the same as example 1, get the battery.

[0048] Figure 1 The flowchart of the preparation method of the phenolic resin based hard carbon of the application; Figure 2 The thermogravimetric curve of comparative example 1 and examples 1-3 (the abscissa is temperature, the ordinate is residual mass fraction, which reflects the thermal decomposition characteristics of the material); Figure 3 The X-ray small-angle diffraction pattern of comparative example 1 and examples 1-3 (the abscissa is scattering vector q, the ordinate is diffraction intensity, which reflects the difference of pore structure of the material); Figure 4The constant current charge-discharge curve graph of the present application comparative example 1 (the abscissa is specific capacity, the ordinate is voltage, and the charge-discharge performance of the traditional hard carbon is embodied); Figure 5 The constant current charge-discharge curve graph of the present application comparative example 1 (the abscissa is specific capacity, the ordinate is voltage, and the charge-discharge performance of the traditional hard carbon is embodied); Figure 6 The constant current charge-discharge curve graph of the present application comparative example 1 (the abscissa is specific capacity, the ordinate is voltage, and the charge-discharge performance of the traditional hard carbon is embodied); Figure 7 The constant current charge-discharge curve graph of the present application comparative example 1 (the abscissa is specific capacity, the ordinate is voltage, and the charge-discharge performance of the traditional hard carbon is embodied); Figure 8 The constant current charge-discharge curve graph of the present application comparative example 1 (the abscissa is specific capacity, the ordinate is voltage, and the charge-discharge performance of the traditional hard carbon is embodied);

[0049] Figure 1 The complete steps from the preparation of mixed aldehyde to the carbonization of hard carbon are clearly shown; Figure 2 The thermal gravimetric curve of the present application comparative example 1 (the abscissa is specific capacity, the ordinate is voltage, and the charge-discharge performance of the traditional hard carbon is embodied); Figure 3 The X-ray small-angle diffraction pattern of the present application comparative example 1 (the abscissa is specific capacity, the ordinate is voltage, and the charge-discharge performance of the traditional hard carbon is embodied); Figures 4-7 The charge-discharge curve of the present application comparative example 1 (the abscissa is specific capacity, the ordinate is voltage, and the charge-discharge performance of the traditional hard carbon is embodied); Figure 8 The rate performance curve of the present application comparative example 1 (the abscissa is specific capacity, the ordinate is voltage, and the charge-discharge performance of the traditional hard carbon is embodied); Figure 8 It can be seen that under different rates of 20mA / g-2A / g, the capacity retention rate of example 3 is significantly higher than that of other samples, especially at high rates of 1A / g and 2A / g, the capacity of example 3 can still maintain a high level, indicating that the continuous conductive network formed by carbon nanotubes greatly improves the ion and electron transmission speed, and effectively improves the rate performance.

[0050] The phenolic resin-based hard carbon prepared in Examples 1 to 3 and Comparative Example 1 was compared in terms of physical structure parameters, and the comparison results are shown in Table 1. The batteries prepared in Examples 1 to 3 and Comparative Example 1 were tested for electrochemical performance, and the test results are shown in Table 2. As shown in Table 1, after the addition of furfural (Examples 1, 2 and 3), the closed pore volume of the hard carbon was significantly higher than that of Comparative Example 1, indicating that furfural as a soft template can effectively increase the number of closed pores. In Example 3, the closed pore volume was further increased due to the addition of carbon nanotubes, and the carbon residue rate was close to that of Example 3, indicating that the addition of carbon nanotubes does not affect the thermal decomposition process of the material and does not destroy the closed pore structure. As shown in Table 2, the reversible discharge capacity of Examples 1 and 2 was significantly improved compared with Comparative Example 1, indicating that the increase in the number of closed pores can effectively improve the sodium storage capacity. In Example 3, the reversible discharge capacity was further improved to 418.4 mAh / g due to the synergistic effect of the closed pore structure and the conductive network, and the first coulombic efficiency remained above 84%, without a significant decrease, balancing the capacity and energy utilization efficiency.

[0051] Table 1, comparison of physical structure parameters Table 2, electrochemical performance test In the present application, phenolic resin prepolymer is synthesized by liquid mixing of formaldehyde and furfural and alkaline catalysis, uniform closed pore structure is formed by using furfural as a soft template, and continuous conductive network is constructed by adding carbon nanotubes in the prepolymer stage, thereby realizing the simultaneous improvement of the reversible capacity and rate performance of the hard carbon. The preparation method is simple in process and low in cost, and is suitable for industrial production. The negative electrode sheet and battery using the hard carbon have excellent electrochemical performance and have a wide application prospect.

[0052] Obviously, the above examples of the present application are only examples for clearly illustrating the present application, and are not intended to limit the embodiments of the present application. Based on the above description, other different forms of changes or variations can be made by those skilled in the art. Here, it is not necessary or possible to exhaust all the embodiments. Any modification, equivalent replacement and improvement made within the spirit and principles of the present application shall be included in the protection scope of the claims of the present application.

Claims

1. A method for preparing phenolic resin-based hard carbon, characterized in that, Includes the following steps: S1. Mix formaldehyde and furfural to obtain a mixed aldehyde solution; S2. The mixed aldehyde and phenol are added to a solution containing an alkaline catalyst to react and generate a liquid phenolic resin prepolymer. S3. Add carbon nanotubes to the liquid phenolic resin prepolymer and disperse the carbon nanotubes in the liquid phenolic resin prepolymer to obtain a second prepolymer; S4. The second prepolymer is cured to obtain the cured resin; S5. Carbonize the cured resin to obtain phenolic resin-based hard carbon.

2. The method for preparing phenolic resin-based hard carbon according to claim 1, characterized in that, In step S1, the molar ratio of formaldehyde to furfural is a:(10-a), where the value of a ranges from 0 to 10.

3. The method for preparing phenolic resin-based hard carbon according to claim 1, characterized in that, In step S2, the mass ratio of the mixed aldehyde to the phenol is (5~55):

100.

4. The method for preparing phenolic resin-based hard carbon according to claim 1, characterized in that, In step S2, the alkaline catalyst is one or more of LiOH, NaOH, and ammonia water, and the molar amount of the alkaline catalyst added is 10% to 20% of the molar amount of phenol added.

5. The method for preparing phenolic resin-based hard carbon according to claim 1, characterized in that, In step S3, the mass of the carbon nanotube is 0.5% to 2% of the total mass of the formaldehyde, furfural, and phenol.

6. The method for preparing phenolic resin-based hard carbon according to claim 1, characterized in that, In step S5, the cured resin is placed in a tube furnace under a nitrogen atmosphere and heated to 1000-1500°C at a heating rate of 1-5°C / min, and carbonized for 1-2 hours to obtain phenolic resin-based hard carbon.

7. The method for preparing phenolic resin-based hard carbon according to claim 1, characterized in that, In step S5, furfural serves as a soft template, forming a uniformly dispersed nanoporous structure during carbonization; the carbon nanotubes form a continuous conductive network after carbonization, constituting an ion or electron transport path with the nanoporous structure.

8. A negative electrode sheet, characterized in that, The device includes an electrode material and a current collector. The electrode material comprises an active material, a conductive agent, a binder, and a current collector. The active material is phenolic resin-based hard carbon prepared according to any one of claims 1 to 7. The mass ratio of the active material, the conductive agent, and the binder is (80 to 95): (2 to 10): (3 to 10). The electrode material is coated on the surface of the current collector.

9. The negative electrode sheet according to claim 8, characterized in that, The conductive agent is one or more of Super-p, acetylene black, and Ketjen black; the binder is one or more of sodium alginate, sodium carboxymethyl cellulose, and styrene-butadiene rubber.

10. A battery, characterized in that, It includes a negative electrode, a positive electrode, and an electrolyte, wherein the negative electrode is a negative electrode sheet as described in any one of claims 8 to 9.